Motivasi Belajar Siswa yang Berlatar Belakang Budaya Melayu dan Jawa - Hasgimianti 1; Ramtia Darma Putri; Raja Rahima MRA (Educational Guidance and Counseling Development Journal, 2018)
Education is a process that students can use to develop their own potential.This was a descriptive comparative research which applied quantitative method. The essence of education is learning. There is no education without learning activities. Student learning motivation is influenced by the cultural background. By Slovin formula followed by simple random sampling technique, 200 students were choosen as the sample at SMP Negeri 1 Siak Hulu Kabupaten Kampar in Academic Year 2015/2016. The data gathered were analyzed by using descriptive statistic and MANOVA (multivariate analysis of variance). The result of the research indicated that: The students' learning motivation with Malaynese cultural backgrounds are in the high category; The students' learning motivation with Javanese cultural backgrounds are are in very high category; and There is no significance different attention of parents between  with Malaynese and Javanese cultural backgrounds, while there are siginificant differences in learning motivation. Learning motivation among students who Malaynese cultural backgrounds and Javanese cultural backgrounds. between the students' cultural backgrounds Malaynese and Javanese